A breathing MOF: direct crystallographic observation of the site-selective C(sp3)–H functionalization. Issue 57 (27th May 2016) - Shi, Dongying; Zeng, Le; Ming, Zheng; He, Cheng; Meng, Changgong; Duan, Chunying
Abstract : A 3D breathing MOF was synthesized for light-driven acceleration of the site-selective C(sp 3 )–H activation. The 1D channels of the assembled MOF can encapsulate reaction substrates via a breathing process that were observed by single-crystal X-ray analyses. Abstract : A 3D breathing MOF was synthesized by hierarchical methods for light-driven acceleration of the site-selective C(sp 3 )–H activation. The 1D channels of the assembled MOF can encapsulate the reaction substrates via a breathing process that was observed by single-crystal X-ray analyses. The weak interactions between the encapsulated substrate and the photoactive center facilitated the in situ generation of the active alkyl radicals.